2009
DOI: 10.1007/s11255-009-9584-3
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of microRNA in bladder tumor tissue is not common

Abstract: MicroRNAs (miRNAs) have recently been shown to down-regulate gene expression by targeting mRNA translation and to play a critical role in tumorigenesis; how they regulate bladder tumor development, particularly in patients, is, however, poorly understood. The difference in miRNA expression in a bladder tumor compared with healthy tissue from the same patients was examined using microRNA arrays in seven patients. Here, we showed that up-regulation of miRNA was not commonly found in this limited number of patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(45 citation statements)
references
References 35 publications
(38 reference statements)
4
41
0
Order By: Relevance
“…Although non-differential expression of miR-30c was observed in cervical cancer cell lines (22) and nasopharyngeal carcinoma tissues (23) compared to the normal controls, most studies have suggested that miR-30c acts as a tumor suppressor and is weakly expressed in cancers such as breast cancer (24), bladder cancer (14), medulloblastoma (15) and clear-cell renal cell carcinoma (25), depending on the tissue context. In this report, we demonstrated the antitumor role of miR-30c in endometrial cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although non-differential expression of miR-30c was observed in cervical cancer cell lines (22) and nasopharyngeal carcinoma tissues (23) compared to the normal controls, most studies have suggested that miR-30c acts as a tumor suppressor and is weakly expressed in cancers such as breast cancer (24), bladder cancer (14), medulloblastoma (15) and clear-cell renal cell carcinoma (25), depending on the tissue context. In this report, we demonstrated the antitumor role of miR-30c in endometrial cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA was isolated using TRIzol reagent (Invitrogen) and then both miRNA and mRNA were reversetranscribed to cDNA with the Reverse Transcriptase M-MLV kit (Takara, China). The stem-loop RT primer for miR-30c was 5'-GTCGTATCCAGTGCAGGGTCCGAGTATTCGC ACTGGATACGACGCTGA-3' (14). U6 small nuclear RNA was used as an internal control.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The decrease in expression of 4 miRNAs is common for all bladder tumors regardless of cancer stage or tumor differentiation. miR-26 may therefore be a significant marker in bladder cancer (20). Maillot et al observed that E2-repressed miR-26a and miR181a regulated numerous genes associated with cell growth and proliferation through estrogen receptors and transcription factors.…”
Section: Mir-26 and Tumors: Down-and Up-regulationmentioning
confidence: 99%
“…Therefore, by targeting antiapoptotic gene (Cdc42,p85a,Mcl1 and Tcl1) and enhancing the inhibiting of tumor transcription, miR-29 chould inhibits the tumor growth effectively . In several researches, the genetic screening showed that the expression of miR-29 a/c in bladder cancer was down-regulated (Dyrskjot et al, 2009;Friedman et al, 2009;Wang et al, 2010). Baffa R et al showed that the expression of miR-29a/b was up-regulated in paired primary and metastatic cancers.…”
Section: Introductionmentioning
confidence: 99%